Development of mobile magnetic imaging system based on 1-D hall sensor array - Ng, Wei Shin (2012)
Non-destructive evaluation (NDE) is one of the most common methodologies in the industries proposed to examine the properties of ferromagnetic materials. The NDE technique includes some kind of microscopy to examine the external surfaces of specimens in detail which rely upon magnetic, ultrasonic and radiographic methods. Therefore, NDE technique can be used to perform shapes evaluation of ferrous objects without permanently altering its characteristic. The NDE technique used in this thesis for shapes evaluation is based on the magnetization characteristic of ferrous objects. This thesis describes the development of prototype Mobile Magnetic Imaging System applying the NDE technique for the shapes evaluation of ferrous objects. The Mobile Magnetic Imaging System is able to evaluate the shapes of ferrous objects underneath a non-ferromagnetic surface with the application of magnetic imaging technique proposed in this research. The magnetic imagings for the shapes of ferrous objects are accomplished by performing the 2-D contour plot with 2-D array matrix of induced voltage signal, VH and magnetic field, B. The operation of Mobile Magnetic Imaging System is based on the magnetic flux leakage testing (MFLT) principle performed on the surface of ferrous objects. As the system navigates across a ferrous object, the permanent magnets on the system magnetize the ferrous object. The magnetized ferrous object forms the magnetic circuit with permanent magnets, thus, develops the closed loop flow of magnetic flux, m. The 1-D Hall sensor array on the system is exposed to the magnetic field, B caused by the flow of magnetic flux, m from permanent magnets to the ferrous object. The 1-D Hall sensor array consists of linearly integrated solid state Hall effects sensors to detect the magnetic field, B and translate to Hall induced voltage signals, VH. The Hall induced voltage signals, VH from 1-D Hall sensor array are constructed into a 2-D array matrix which is employed for magnetic imaging. Lastly, the prototype of the Mobile Magnetic Imaging System is presented. In addition, the performance parameters of Mobile Magnetic Imaging System are identified which include the size of the specimen under evaluation, moving speed of system and thickness of non-ferromagnetic surface above ferrous objects. Therefore, experimental results to study the performance of Mobile Magnetic Imaging System are presented in this thesis. Firstly, it presents the ability of the system in visualizing the shapes of ferrous object specimens with magnetic images. In addition, the improvements towards magnetic imaging technique of ferrous objects are proposed by considering the absolute value of induced voltage signals, |VH| and magnetic field, |B|. Secondly, the result presents the ability of the system to visualize the shapes of actual ferrous objects employing improved magnetic imaging technique. Lastly, the effect of perpendicular gap towards accuracy of Mobile Magnetic Imaging System in shapes evaluation is studied. Based on the experimental results, the optimized perpendicular gap for shapes evaluation is at 10mm. In summary, the Mobile Magnetic Imaging System is proven to be able to visualize the shapes of ferrous objects embedded underneath a non-ferromagnetic surface.